Grief & Personal Growth: Reflection from Quran, Hadith and Modern Medicine - Raduan, NJN; Rosly, NHM; Razali, ZA; Al Siddiq, M; Salleh, MR (INT Islamic Univ Malaysia, Kulliyyah Medicine, 2024)
Indexed by Scopus